IMPLEMENTASI ALGORITMA ELGAMAL DALAM SISTEM LOCK BRANKAS BERBASIS MIKROKONTROLER ATMEGA16 DAN SMARTPHONE ANDROID - Muhammad Rofiq; Bambang Tri Wahjo Utomo (Jurnal Ilmiah Informatika, 2016)
Most of Safes lock system is still using conventional methods nowadays. The conventional method leads to the safes’ burglary. Some of the causes are the safes’ code that can be tracked easily and the key can be duplicated. Previous research on safes’ security has ever been done. The weakness of the study is there is no security system using cryptographic algorithms for data security. The development of a safes security system by implementing ElGamal algorithms is done by following the engineering approach with the stages of methods analysis and design system, implementation and testing of the analysis and the discussion of the overall system. In the analysis and design of mathematical models using ElGamal algorithms, uses fast powering theorems and applications design uses Object OrientedProgramming. In the analysis of hardware refers to the datasheet and calculation of the value of electrical characteristics of the circuit. In the safes lock system, the outcome of the research is a safes prototype which is equipped with enhancements that include a series of processing algorithms, the data viewer, a wireless data transfer device, the Android smartphone as a system of user authorization. For the lock safes systems is using a locked solenoid. The control system is done by a lock safes android smartphone via Bluetooth communication. The test results also indicate the system will open the safes if the code and the public key is entered correctly, and the system will not open if one of the codes or the public-keys are wrong or both are wrong.